Optical Characterization of Intralipid 20% at Wavelength 405nm (Journal of Hama University, 2020)
The aim of this study is the determination of Intralipid 20% optical parameters at wavelength 405nm. Therefore, two methods were used, the first one was a modified Kubelka-Munk model and the second one was Mie theory. For this purpose, a single integrating sphere system was set up to determine the diffuse reflection and transmission spectrum and collimated transmission spectroscopy to determine the collimated transmission spectrum. Comparison of scattering coefficients which  are calculated by these two methods were matched, and proved the applicability of a modified Kubelka-Munk model with a single integrating sphere system and Cauchy equation for estimation the real part of fat emulsion's refractive index. Besides to calculate absorption coefficient, anisotropy factor and imaginary refractive index depend on the coefficient absorption.